(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Oncological processes of the head and neck are a large number of tumors that have a different course and require different treatment. In advanced stages, this treatment can lead to the loss of vital functions and disrupt the appearance of a person with the appearance of bone and soft tissue defects [3]. But if this process is detected at the very beginning with an asymptomatic course or at stage I of the disease, then in 95-97% of cases, the neoplasm can be removed without disability [5]. At this stage in the development of modern medicine, with the help of radiation therapy and endoscopic surgery, it is possible to effectively treat oncological processes of the head and neck at stages I and II of the disease [2, 6]. With regard to the use of endoscopic surgery, the risk of developing psychological trauma in patients is reduced due to the absence of large incisions [8]. This article analyzed, examined and questioned 217 patients, aged 30 to 89 years, residents of the city of Tashkent and the region with a confirmed diagnosis of a malignant neoplasm of the oropharyngeal zone, of which 127 were men and 90 were women. Of the total number of patients, 30% initially turned to a dentist. The greatest number of cases of malignant neoplasms is determined at the age of 50 to 69 years in both sexes. Patients living in Tashkent were statistically significantly (p<0.05) less likely to meet, in the aggregate, in terms of negotiability than patients living in the Tashkent region. Primary T1 tumors were statistically significantly (p<0.05) more common. The absence of regional metastases (N0) was statistically significant (p<0.05) more often. Also, neoplasms with a high degree of cell differentiation (G1) were more often statistically significant. Most often (p<0.05) malignant neoplasms were localized on the tongue and lips. The keratinizing form of squamous cell carcinoma was statistically significantly (p<0.001) more common.